Comparison of functional outcomes after total thyroidectomy and completion thyroidectomy: Hypoparathyroidism and postoperative complications. Issue 1 (February 2019) - Park, Young Min; Kim, Jeong-Rok; Oh, Kyung Ho; Cho, Jae-Gu; Baek, Seung-Kuk; Kwon, Soon-Young; Jung, Kwang-Yoon; Woo, Jeong-Soo
Abstract: Objective: This study aimed to investigate differences in functional outcomes of postoperative complications and hypoparathyroidism between patients who underwent completion thyroidectomy (CT) after thyroid lobectomy or total thyroidectomy (TT) as an initial treatment. Materials and methods: We retrospectively analyzed the differences of functional outcomes after completion thyroidectomy and total thyroidectomy without lymph node dissection. We reviewed the medical records of 396 patients who underwent CT or TT for thyroid disease at Korea University Guro Hospital from March 2002 to August 2016. Results: Of the 396 patients, 32 underwent CT and 364 underwent TT. There were 72 male patients and 324 female patients. Transient hypoparathyroidism was observed in 4 (9.4%) of the CT patients and 97 (26.6%) of the TT patients, with a statistically significant difference (p = 0.031). Permanent hypoparathyroidism was observed in 1 patient (3.1%) in the CT group and in 13 patients (3.6%) in the TT group, which was not significantly different. There were no significant differences in the postoperative complication of temporary recurrent laryngeal nerve injury, wound infection, and hematoma between two patients group. Conclusion: The incidence of transient hypoparathyroidism in CT patients was significantly lower than in TT patients. These safety and functional superiority of CT should be considered when determining the scope and extent of operation in patients requiring surgery for thyroid disease.